Significant Results . Space Makes a Difference Increasing Student Academic Engagement Levels - Scott-Webber, Lennie; Konyndyk, Roger; French, Raechel; French, Jim (European Scientific Journal, ESJ, 2018)
Our team consisting of researchers, designers and a statistician are working to establish statistically reliable and valid survey instruments for use in post building occupancy for schools housing students and educators in grades nine to twelve. Two indexes are being created, a Student Engagement IndexÂ© and a Teachers Engagement IndexÂ©. Our research question is, â€œCan we demonstrate that the design of the built environment for grades 9-12 impacts student academic engagement levels?â€ The sample for this survey was four high schools in the USA, in fall 2017. A time-honored Post- Occupancy methodology was used. Findings had strong indicators showing the buildingsâ€™ design makes a statistically significant difference regarding student academic engagement levels. Results were excellent on reliability and have convergent validity, with the exception of the last two questions. Statistical evidence from students and educators across all schools, grades, and genders that the buildingsâ€™ designs impact their academic engagement levels (p<.0001). When active learning is used students recognize the impact. Concluded that for educators, the overall â€œcultureâ€ of the school is a far moreÂ important factor for teacher engagement than the physical layout. Seen as a real effect, all respondents acknowledged that the physical environment impacted engagement in their teaching and learning practices (p<.0001),Â significant result indicating that space makes a difference and increases student academic engagement levels.